The writing centre: A site for discursive dialogue in Management Studies - Arbee, Aradhna; Samuel, Michael Anthony (South African Journal of Higher Education, 2016)
This article contributes to the ongoing conversation, in this journal and others, about academic literacy development in higher education. It reports on a small-scale quantitative study of the effect of writing centre support on students’ academic performance, in the disciplinary context of Management Studies. The study generates questions and areas for reflection about how to assess the ways in which writing centres can become more valuable programmatically, institutionally, theoretically and methodologically. Its uniqueness arises from the attempt to look at the development of academic literacy writing competences not during the transition from school into university, but at the exit point of an academic bachelors’ degree programme. It raises questions such as: Is there a value for academic discourse induction even at this exit stage, and what impact does it have on the development of writing competences? How do we know this impact?